Revisiting the causal nexus between savings and economic growth in India: An empirical analysis - Suresh Kumar Patra; Dogga Satyanarayana Murthy; Mahendra Babu Kuruva; Avipsa Mohanty (EconomiA, 2017)
This paper attempts to analyze the long run association between savings and growth; and investigates the causality issue in Indian context for the period 1950–51 to 2011–12. Firstly, the study identifies the structural break in the year 1980 by employing Bi-Perron test with unknown time. Further, it examines the association and the direction of causality between savings and real economic activity. The empirical evidence of the study suggests that savings boost the real activity both in the pre and post break period in the long run, while economic growth causes saving in the short run in the pre break period. Thus, the present study brings evidence in favour of the neoclassical exogenous and the post-neoclassical endogenous growth models and suggest that both the incentive-based measures and the productivity-based measures would be useful to generate higher savings and reinforce the acceleration of income and growth.
Keywords: 330; Savings; Economic growth; Structural break; Poupança; Ggrowth econômico; Ruptura estrutural